USING THE SMARTPHONE APPLICATION FOR PREGNANCY CARE: A LITERATURE REVIEW - Sustamy, Raffiky Pinandia; Pratiwi, Rizqi D; Wahyuni, Sri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Smartphones are new media that provide greater benefits than conventional health education. It provides ease and quick access information for users and they may repeat any time. This study aims to analyze the use of various applications related to assessment care, including pregnancy. Methodology: The literatures was collected from e-databases such as Science direct, PubMed, and Google Scholar. Journal criteria used by using RCT (Randomized Controlled Trials (RCTs) techniques and English-language journals. 5 international journal articles were found by using the keywords ?smartphone applications? and ?pregnancy care?. The journal had to be conducted in 2014-2019. Results: The smartphone application was a medium that used to get information easier, faster and efficient. Those 5 journal articles were conducted in Indonesia (1 journal), Australia (3 journals), and USA (1 journal). It has been proven in 5 research articles to show effectiveness results in information acquisition, management of anxiety, weight management, management of antenatal care visits and management of childbirth preparations, thus helping pregnant women to optimally care for pregnancy. Overall, all of the applications were effective as the health promotor media. Conclusion: The future recommendations are needed to improve the materials and the information in term of pregnancy. The usage of application as health education media should be develop for low middle-income household.